Decompression for Management of Keratocystic Odontogenic Tumor in the Mandible - de Melo, Willian Morais; Pereira-Santos, Darklilson; Sonoda, Celso Koogi [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Lippincott Williams & Wilkins, 2012)
Keratocystic odontogenic tumor (KCOT) is a benign intraosseous neoplasm of odontogenic origin with high recurrence rate. To date, various conservative or aggressive management strategies have been suggested as a method of treatment. Decompression is a conservative method that has been used in the treatment of large odontogenic cysts. The present paper reports a case of KCOT located in the mandible and discusses the importance of its management using conservative methods. The authors present a case of a 38-year-old patient with a KCOT located in the right mandibular angle and ascending ramus, which was treated by decompression followed by enucleation and curettage. The lesion did not recur during a follow-up period of 3 years after surgery. Preserving important structures of the bone and soft tissue decompression is a method with low morbidity. In addition, according to the literature, decompression has a success rate at least as high as the one of most aggressive treatments.
Keywords: Benign tumors; jaw cyst; mandible; odontogenic keratocyst; surgical management